APLIKASI SISTEM PAKAR DIAGNOSIS KERUSAKAN DAN SIMULASI PERAKITAN KOMPUTER BERBASIS WEB MENGGUNAKAN METODE FORWARD CHAINING - Agie Nugraha Pratama; Rysa Sahrial (JURNAL LENTERA ICT, 2024)
A computer is a set of objects that we can find in various places, especially in offices or homes as a tool to help complete various tasks. In Greek, a computer is called "computare" which means "to calculate" so that the simple meaning of a computer is a tool for carrying out arithmetic calculation processes, while in general it is electronic equipment that functions as data input, then processes it and provides information output in text form. , images, sound and video. The Web-based Damage Diagnosis Expert System Application and Computer Assembly Simulation Using the Forward Chaining Method is an application that can help users identify damage and make it easier for users to assemble computers. Application of a Web-Based Damage Diagnosis Expert System and Computer Assembly Simulation Using the Forward Chaining Method. In making the system, the paradigm used is a prototype model that uses UML (unified modeling language) as a language for visualization and designing the software to be built, while diagrams are used in analysis and design, namely use case diagrams, activity diagrams, class diagrams and sequence diagrams. Meanwhile, the tools used in developing applications use Viaual Studio, XAMPP, and MySQL In this final project, an Expert System Application for Damage Diagnosis and Simulation of Web-Based Computer Assembly Using the Forward Chaining Method was created to make it easier for users to find out damage to computers and also be able to assemble their own computers using simulationsKeywords: Konter access, pandemi covid-19, extreme programing